Circulating Sex Hormones Are Associated With Gastric and Colorectal Cancers but Not Esophageal Adenocarcinoma in the UK Biobank. (4th March 2021) - McMenamin, Úna C.; Liu, Peipei; Kunzmann, Andrew T.; Cook, Michael B.; Coleman, Helen G.; Johnston, Brian T.; Cantwell, Marie M.; Cardwell, Chris R.
Abstract : INTRODUCTION: Gastrointestinal cancers show an unexplained male predominance, but few prospective studies have investigated sex hormones and gastrointestinal cancer risk. This study aimed to determine the impact of circulating sex hormones on risk of esophageal, gastric, and colorectal cancers in men and women. METHODS: We included 219, 425 men and 147, 180 women from the UK Biobank. Sex hormones were quantified using chemiluminescent immunoassay. Gastrointestinal cancers were identified from cancer registry linkages. Sex hormone concentrations and risk of gastrointestinal cancers were investigated using Cox proportional hazards regression. RESULTS: During the 10 years of follow-up, 376 esophageal adenocarcinoma, 108 esophageal squamous cell carcinoma, and 333 gastric and 2, 868 colorectal cancer cases were identified. Increased hazard ratios (HRs) were found for sex hormone–binding globulin (SHBG) and risk of gastric cancer in men (Q4 vs Q1 HR 1.43, 95% confidence interval [CI] 0.95–2.17, Ptrend = 0.01). Free testosterone was inversely associated with esophageal squamous cell carcinoma in women (Q4 vs Q1 HR 0.32, 95% CI 0.11–0.98, Ptrend = 0.05). For colorectal cancer, SHBG was associated with a reduced risk among men (Q4 vs Q1 HR 0.89, 95% CI 0.77–1.03, Ptrend = 0.04) and free testosterone concentrations was associated with a reduction in risk among women (Q4 vs Q1 HR 0.80, 95% CI 0.66–0.97, Ptrend = 0.01). No associations were found for esophageal adenocarcinoma. DISCUSSION: In this large prospective investigation of prediagnostic sex hormones and risk of gastrointestinal cancers, men with higher SHBG concentrations had higher gastric, yet lower colorectal, cancer risks, whereas women with higher free testosterone levels had a lower risk of esophageal squamous cell carcinoma and colorectal cancer.